Beyond the visible: Rethinking femininity through the femme assemblage. Issue 3 (August 2018) - McCann, Hannah
While there has been much focus on the disempowering and incapacitating effects of 'normative' femininity, less attention has been paid to the queer possibilities of femininity. Queer femme has been proposed by some as a key site for rethinking femininity. Extending upon these discussions, and drawing on interviews conducted with queer femmes in Australia in 2013, this article proposes focusing on affective dimensions to deepen our understanding of queer femme as more than an identity, but rather, as assemblage Working from the basis of assemblage, this article examines exactly how and why femme bodies queer femininity. However the article also argues that where queer femme discourse distances itself from non-femme, or 'normative', femininity, it misses an opportunity for advocating for a different approach to gender presentation within a broader collective. The central argument of this article is that from an affective theory of queer femme as assemblage, we can better understand both queer femme identity and the attachments to femininity that people maintain more generally, without relying on a binary logic that proclaims femininity as only disempowering or empowering, queer or not queer enough.